TINGKAH LAKU PUERULUS LOBSTER PASIR (Panulirus homarus) YANG DIPELIHARA PADA WARNA WADAH BERBEDA - dudi lesmana; Fia Sri Mumpuni (JURNAL MINA SAINS, 2022)
Cannibalism is one of the factors contributing to the slow growth of lobsters. Cannibalism refers to the practice of one member of a species eating all or a portion of another member of the same species for nourishment. Cannibalism results in bodily deformities including missing fins and skin sores. Cannibalism is stimulated by the chemicals that are released from injured skin (amino acids). The level of cannibalism is said to be triggered by the container's mismatched color. This study set out to ascertain the behavior of lobster, including how frequently they molt and how much cannibalism occurs. A completely randomized design (CRD) with 4 treatments and 3 repetitions was employed in this study. It is well known that one factor in cultivating operations to boost output is the color of the tank. Color of the backdrop water in natural ecosystems to identify feed. In comparison to other treatments, lobsters raised with color tended to molt more frequently (69.33±0.14%) (P <0.05). In comparison to the treatment, lobsters raised in transparent/control containers had a greater percentage of cannibalism (36.00±0.33%) (P< 0.05)